2019
DOI: 10.1111/mpp.12775
|View full text |Cite
|
Sign up to set email alerts
|

Pseudozyma aphidis activates reactive oxygen species production, programmed cell death and morphological alterations in the necrotrophic fungus Botrytis cinerea

Abstract: Summary Many types of yeast have been studied in the last few years as potential biocontrol agents against different phytopathogenic fungi. Their ability to control plant diseases is mainly through combined modes of action. Among them, antibiosis, competition for nutrients and niches, induction of systemic resistance in plants and mycoparasitism have been the most studied. In previous work, we have established that the epiphytic yeast Pseudozyma aphidis inhibits Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…P. guilliermondii was shown to strongly adhere to hyphae of the plant pathogen B. cinerea and to cause hyphal collapse, presumably due to the secretion of hydrolytic enzymes such as glucanases (see above) (Wisniewski et al 1991). Similarly, the yeast-like Ustilaginomycete Pseudozyma aphidis parasitises the powdery mildew pathogen Podosphaera xanthii and B. cinerea (Calderon et al 2019; Gafni et al 2015). The genus Saccharomycopsis , comprising predacious yeasts directly feeding on their prey, was studied with respect to biocontrol of different Penicillium species as well as clinically relevant yeasts (Junker et al 2017, 2018, 2019; Lachance and Pang 1997; Pimenta et al 2008).…”
Section: Mechanisms Underlying the Biocontrol Activity Of Yeastsmentioning
confidence: 99%
“…P. guilliermondii was shown to strongly adhere to hyphae of the plant pathogen B. cinerea and to cause hyphal collapse, presumably due to the secretion of hydrolytic enzymes such as glucanases (see above) (Wisniewski et al 1991). Similarly, the yeast-like Ustilaginomycete Pseudozyma aphidis parasitises the powdery mildew pathogen Podosphaera xanthii and B. cinerea (Calderon et al 2019; Gafni et al 2015). The genus Saccharomycopsis , comprising predacious yeasts directly feeding on their prey, was studied with respect to biocontrol of different Penicillium species as well as clinically relevant yeasts (Junker et al 2017, 2018, 2019; Lachance and Pang 1997; Pimenta et al 2008).…”
Section: Mechanisms Underlying the Biocontrol Activity Of Yeastsmentioning
confidence: 99%
“…tomato and Xanthomonas campestris pv. campestris [ 61 ].Those metabolites have not yet been identified but they are largely lipophilic and found to induce reactive oxygen species (ROS) accumulation and PCD in B. cinerea hyphal cells [ 62 ].…”
Section: Antibiosis: Fungal Metabolites As a Source For New Pesticmentioning
confidence: 99%
“…In contrast, we have shown that to control gray mold disease caused by B. cinerea, P. aphidis remains as a yeast-like structure and thus does not coil around B. cinerea hyphae [ 44 ]. However, the P. aphidis cells could adhere to B. cinerea hyphae and secrete lytic enzymes and proteases when exposed to B. cinerea cell wall extract, suggesting that close proximity enhances the antibiotic activity and cell wall-degrading enzyme efficiency, thereby also supporting the parasitism dogma [ 62 ]. The dimorphic switch from hypha-like to yeast-like is a well-known phenomenon in fungal pathogens [ 128 ].…”
Section: Mycoparasitisim and Cell Wall-degrading Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Like all aerobic organisms, plants have well‐developed metabolic pathways that utilize their energetic potential in the presence of oxygen (Calderón, Rotem, Harris, Vela‐Corcía, & Levy, 2019; Navrot, Rouhier, Gelhaye, & Jacquot, 2007). One potentially damaging effect of metabolism is the deleterious production of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), during normal respiration, photosynthesis, N fixation, and abiotic stress responses (Ahmad, Jaleel, Salem, Nabi, & Sharma, 2010; Chen, Zhang, & Zhang, 2019; Choudhury, Rivero, Blumwald, & Mittler, 2017).…”
Section: Introductionmentioning
confidence: 99%